"For whom the watch tolls": Usability and feasibility of a smartwatch‐based intervention for people with dementia. (December 2021) - Köhler, Stefanie; Goerss, Doreen; Teipel, Stefan J.
Abstract: Background: Zero‐effort technologies (ZET) are promising for supporting people with cognitive impairment. One needs to consider the user's cognitive abilities, needs and usability‐requirements to secure the acceptance of ZET by this vulnerable group. In our study, we aimed to evaluate the feasibility and usability of a ZET technology that gave acoustic and visual instructions to people with cognitive impairment. Method: Following the Values Sensitive Design approach, we conducted 30 semi‐structured interviews (including people with cognitive impairment, relatives, and healthcare professionals) focusing on assistive technology in institutional care. Based on these interviews, we derived the design of a real‐world experiment to test a ZET system's feasibility and usability. The experiment consisted of two different instructions representing activity of daily living (drinking water) and cognitive activation (circling bells on a sheet‐according to the Bell's Test) delivered by a smartwatch. During the intervention, participants were alone but observed via camera‐live‐stream and videotaping to evaluate interventions' success in real time and offline. The interventions were divided into "regular" (1x vibration & ringtone, text & picture) and "intensive" (multiple vibration & ringtone, text & acoustic instruction & animated picture) mode. All participants filled a usability‐questionnaire after the experiment. Result: Preliminary results in five (3 female, MMSE mean: 24.6, age mean: 75.2) of the 40 intended participants showed the ability to complete the drinking‐task. The smartwatch design was evaluated as comfortable but too big. Participants who preferred vibration alert indicated that a ringtone may let them be perceived as person with need for help. In contrast, only participants with the intensive mode (n=2) completed the Bell's test task. Only one participant wished for more interaction with the smartwatch. All participants agreed on additional calendar and reminding function as well as making emergency calls as useful features of the smartwatch system Conclusion: People with cognitive impairment accept instructions given by a smartwatch. Participants preferred a scenario where they were not required to interact with the system, supporting the notion of ZET. Talking to the future users before designing the experiment helped to create a useful experimental design to assess user acceptance and identify further system requirements.